Screening of Rice (Oryza sativa L.) Genotypes at Reproductive Stage for their Tolerance to Salinity (The Agriculturists, 2018)
Soil salinity is one of the most devastating environmental stresses for rice production in the coastal areas of Bangladesh. Improvement in salt tolerance of rice is an important way for the economic utilization of coastal zones. An experiment was conducted at the vinyl house of the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Bangladesh during December 2016 to April 2017 to determine the effects of different salinity levels on the yield and yield components of some rice (Oryza sativa L.) genotype sand finally, screening of rice genotypes for salt tolerance. The experiment containing four treatments was laid out in a complete randomized design with five replications. The treatments were four levels of saline water with electrical conductivities at control (0.3 dSm-1), 5, 10 and 15dSm-1. Based on screening at germination stage, relatively salt-tolerant eleven genotypes with two check varieties were used in this experiment. The study showed that increase in salinity level significantly decreased yield and yield contributing characters of rice. However, among the eleven, three genotypes (Chapali, Patnai 23 and Soloi) were considered as moderately salt tolerant at 15 dSm-1 on the basis of their yields and yield contributing characteristics such as plant height reduction, total tiller reduction, effective tiller reduction, reduction of fertile grains per panicle, grain yield and relative grain yield. Therefore, Chapali, Patnai 23 and Soloi might be recommended as moderately salt tolerant rice genotypes. The Agriculturists 2018; 16(1) 65-77